'Being yourself': everyday ways of doing and being gender in a 'rights-respecting' primary school. Issue 2 (17th February 2019) - Webb, Rebecca
ABSTRACT: This paper engages with some everyday ways of doing and being gender which proceed from a dominant liberal rights policy and practice discourse within one English 'rights-respecting' primary school in England. Drawing on three ethnographic vignettes of data from different spaces within the school, it utilises a Butlerian analytic to interrogate the kinds of subjects that children are entitled and obliged to be as they take up different subject positions proposed to them in the school. The paper engages with this empirical data, to foster and ignite critical sensibilities, especially as these relate to 'taken-for-granted' discourses of children's rights which presume the participation of all children regardless of their differently gendered subjectivities. This analysis puts in question the universal, normative and essentialising effects of the category of the rights-respecting child as always unproblematic and forever productive.